Does Increase in Birth Weight Change the Normal Labor Curve? - Leftwich, Heidi K.; Gao, Weihua; Wilkins, Isabelle (American Journal of Perinatology, 2015)
Objective This study is designed to assess the effect of birth weight on the duration of labor.Study Design Retrospective review of the electronic database created by the Consortium on Safe Labor, reflecting labor and delivery information from 12 clinical centers from 2002 to 2008. Population included all laboring women in the 19 participating hospitals, excluding those with malpresentation, fetal anomalies, elective repeat cesarean, multiple gestations, gestational age less than 34 weeks, and delivery with less than two cervical examinations. Birth weight categories include less than 2,500 g, 2,500 to 3,000 g, 3,000 to 3,500 g, 3,500 to 4,000 g, and greater than 4,000 g. Interval censored regression analysis was used to determine distribution of times for cervical dilation progression in centimeters.Results A total of 146,904 maternal records were reviewed. In nulliparous, traverse times increased as birth weight increased, both in successful trial of labor and also those who ultimately required cesarean delivery (p < 0.01). In multiparous with successful trial of labor, traverse times increased as birth weight increased from 5 to 8 cm (p < 0.01). From 8 to 10 cm, traverse times increased by birth weight, though this was not statistically significant.Conclusion We have shown that in a large cohort of contemporary laboring women, as birth weight increases, progression in labor is, in fact slower.
Keywords: birth weight; labor; pregnancy; contemporary